Rheumatoid Arthritis Recent Research Advances - Smolen, Josef S. 1950-; Kalden, Joachim R. 1937-2021; Maini, Ravinder N. (Springer Berlin Heidelberg, 1992)
Many advances have occurred in the last 5 years especially in understanding genetic susceptibility factors, the role of immune response in chronic arthritis and the relationship between cellular processes that underlie inflammation and tissue damage. All these are dealt with in depth in the individual contributions. Genetics studies included illustrate how studies of HLA genes and genes controlling the autoantibody repertoire may be involved. Environmental factors are believed to be important and studies both in humans and in experimental models on the role of viral and bacterial agents are covered. The fascinating relationship between microbes, dysregulated immune responses and oncogenes are also examined. Since autoimmunity is the key aspect of the immunological response in rheumatoid arthritis, the role of antigens is re-examined as is the part played by immune T and B cells. New areas of clinical application of basic science is well presented in this book, forexample, in examining how markers of cartilage destruction may become important in monitoring disease activity. A chapter reviewing possible future novel therapies is included
Keywords: Rheumatology; Immunology; Orthopedics; Rheumatoide Arthritis